Elevated paleomagnetic dispersion at Saint Helena suggests long-lived anomalous behavior in the South Atlantic - Engbers, Yael A.; Biggin, Andrew J.; Bono, Richard K. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Earth’s magnetic field is presently characterized by a large and growing anomaly in the South Atlantic Ocean. The question of whether this region of Earth’s surface is preferentially subject to enhanced geomagnetic variability on geological timescales has major implications for core dynamics, core−mantle interaction, and the possibility of an imminent magnetic polarity reversal. Here we present paleomagnetic data from Saint Helena, a volcanic island ideally suited for testing the hypothesis that geomagnetic field behavior is anomalous in the South Atlantic on timescales of millions of years. Our results, supported by positive baked contact and reversal tests, produce a mean direction approximating that expected from a geocentric axial dipole for the interval 8 to 11 million years ago, but with very large associated directional dispersion. These findings indicate that, on geological timescales, geomagnetic secular variation is persistently enhanced in the vicinity of Saint Helena. This, in turn, supports the South Atlantic as a locus of unusual geomagnetic behavior arising from core−mantle interaction, while also appearing to reduce the likelihood that the present-day regional anomaly is a precursor to a global polarity reversal.